Contrasting salinity effects of artificial seawater and sodium chloride on Carica papaya L. cultivar Red Lady physiology and growth - Edivan Rodrigues de Souza; Bruce Schaffer; Ana I. Vargas; Aline de Camargo Santos; Edwin Antonio Gutierrez Rodriguez (CABI Agriculture and Bioscience)
Abstract Background Many coastal areas of the world will be impacted by seawater intrusion inland exposing crops to increasing levels of soil salinity. Studies of salinity stress in horticultural crops, including papaya, invariably use NaCl as the salt source, which may not be indicative of seawater. Methods This study compared plant growth, physiological, and nutritional responses, including leaf gas exchange, maximal potential quantum efficiency of photosystem II (the ratio of variable to maximum chlorophyll fluorescence; Fv/Fm), the leaf chlorophyll index (LCI), electrolyte leakage (EL), leaf relative water content (RWC), leaf water potential (Ψw), leaf osmotic potential (Ψo), leaf and root N, P, K, Ca, Mg, Na and Cl contents, and growth of potted ‘Red Lady’ papaya plants, in a calcined clay substrate, irrigated with NaCl or artificial seawater (Instant Ocean®) at six soil electrical conductivity (EC) levels (0, 1, 2, 3, 4 or 6 dS m−1). Results There were slight significant reductions in Ψw, Ψo, net CO2 assimilation (A), stomatal conductance (g s ), and transpiration (Tr) with increasing EC regardless of the salt source. Leaf Ca, Mg, Na and Cl contents and root Mg, Na, and Cl increased significantly with increasing EC levels. For both salt sources, there was an indication of osmotic adjustment and tolerance of papaya up to an EC level of 6 dS m−1. A significant difference between the response to NaCl and artificial seawater was observed for plant height, leaf Mg and Cl contents, and root Mg and Na contents. Conclusion The use artificial seawater may be a better source than NaCl for studying papaya responses to increasing soil salinity.